2020
DOI: 10.1101/2020.03.05.979468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurons in the ventral striatopallidal complex modulate lateral hypothalamic orexin/hypocretin neuron activity: Implications for reward-seeking

Abstract: Feeding is at once both a basic biological need and a function set in a complex system of competing motivational drivers. Orexin/hypocretin neurons are located exclusively within the lateral hypothalamus (LH) and are commonly implicated in feeding, arousal, and motivated behavior, although largely based on studies employing long-term systemic manipulations. Here we show how orexin neurons in freely behaving mice respond in real time to food presentations, and how this response is modulated by differences in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
(64 reference statements)
2
7
0
Order By: Relevance
“…Systemic SB-334867 also reduces yohimbine-(stress)-induced reinstatement of alcohol-seeking (Richards et al, 2008). In line with this, our results also extend recent studies where the orexin system has been associated with the motivation to approach a reward, rather than the actual consumption of the reward (Mitchell et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Systemic SB-334867 also reduces yohimbine-(stress)-induced reinstatement of alcohol-seeking (Richards et al, 2008). In line with this, our results also extend recent studies where the orexin system has been associated with the motivation to approach a reward, rather than the actual consumption of the reward (Mitchell et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Mitchell et al (2020) report that during the approach to food, orexin activity significantly increased but then reverted to baseline level when food consumption started. Furthermore, they suggest that termination of this orexin activity may be mediated by direct and indirect inhibitory signals from the nucleus accumbens to orexin neurons in the lateral hypothalamus (Mitchell et al 2020). Together, this raises the possibility that orexin signalling is more crucial for mediating appetitive behaviour rather than the consumption itself.…”
Section: The Role Of Orexins In Homeostatic and Rewardbased Feedingmentioning
confidence: 83%
“…Another study, using fibre photometry, found that upon physical contact with food, the activity of orexin neurons rapidly reduced, regardless of the taste, textures and caloric content (Gonzalez et al 2016). Similarly, Mitchell et al (2020) report that during the approach to food, orexin activity significantly increased but then reverted to baseline level when food consumption started. Furthermore, they suggest that termination of this orexin activity may be mediated by direct and indirect inhibitory signals from the nucleus accumbens to orexin neurons in the lateral hypothalamus (Mitchell et al 2020).…”
Section: The Role Of Orexins In Homeostatic and Rewardbased Feedingmentioning
confidence: 94%
See 2 more Smart Citations